A herpes simplex virus type 2–encoded microRNA promotes tumor cell metastasis by targeting suppressor of cytokine signaling 2 in lung cancer - Xudong Wang; Shupeng Liu; Zhenhua Zhou; Hongli Yan; Jianru Xiao (Tumor Biology)
Certain viruses use microRNAs to regulate the expression of their own genes, host genes, or both. A number of microRNAs expressed by herpes simplex virus type 2 have been confirmed by previous studies. However, whether these microRNAs play a role in the metastasis of lung cancers and how these viral microRNAs precisely regulated the tumor biological process in lung cancer bone metastasis remain obscure. We recently identified the high expression of an acutely and latently expressed viral microRNA, Hsv2-miR-H9-5p, encoded by herpes simplex virus type 2 latency-associated transcript through microarray and quantitative polymerase chain reaction analyses which compared the expression of microRNAs in bone metastasis from lung cancer with primary lung cancers. We now reported that Hsv2-miR-H9-5p was highly expressed in bone metastasis and closely associated with pathological and metastatic processes of lung cancers. The functions of Hsv2-miR-H9-5p were determined by overexpression which results in an increase in survival, migration, and invasion of lung cancer cells in vitro. We determined that Hsv2-miR-H9-5p directly targeted SOCS2 mechanistically by dual-luciferase reporter assay. Then, we investigated the functions of SOCS2 in the progress of lung cancers. Reduction of SOCS2 dosage by hsv2-miR-H9-5p induced increased migration and invasion of lung cancer cells. Overexpression of SOCS2 inverted these phenotypes generated by hsv2-miR-H9-5p, indicating the potential roles of SOCS2 in Hsv2-miR-H9-5p-driven metastasis in lung cancers. The results highlighted that Hsv2-miR-H9-5p regulated and contributed to bone metastasis of lung cancers. We proposed that Hsv2-miR-H9-5p could be used as a potential target in lung cancer therapy.